Rediscovery of Chloraea multilineolata (Orchidaceae, Chloraeinae), an endangered Peruvian species - Trujillo, Delsy; Edquén , José D.; Rizo-Patrón, Federico; Calatayud, Gloria; Gutiérrez Dipaz, Alfredo; Salazar , Gerardo A. (Instituto de Ecología, A.C., 2023)
Background and Aims: Since its publication, in 1941, Chloraea multilineolata had not been recorded again and the reports of this species in subsequent literature were based on erroneous identifications. In this work, the taxonomic identity of several populations of Chloraea species recorded during recently fieldwork carried on during 2016 and 2019 in southern Peru was studied. Methods: Fresh material and photographic records of the several recently discovered populations of Chloraea were studied and compared with protologues, original material, taxonomic literature, and specimens of Chloraea or digital images of them deposited in Peruvian and foreign herbaria. Key results: The studied populations were determined to represent C. multilineolata. An updated description of the species based on fresh material and the protologue is presented. In addition, color photographic plates illustrating its vegetative and floral morphology, a line drawing of the perianth, information on its habitat, and a map of its known distribution are included, as well as an assessment of its extinction risk using the categories and criteria of the Red List of the International Union for the Conservation of Nature (IUCN). Conclusions: Chloraea multilineolata is endemic to the Peruvian departments of Apurímac, Ayacucho, and Cusco, being restricted to dry inter-Andean valleys between 2000 and 2900 m elevation. Only one of the five known localities is in a protected natural area (Área de Conservación Regional Choquequirao) and the assessment of its conservation status indicates that it should be considered as Endangered.